Copper-Catalyzed Azomethine Imine–Alkyne Cycloadditions (CuAIAC) - Grošelj, Uroš; Požgan, Franc; Štefane, Bogdan; Svete, Jurij (Synthesis, 2018)
Although the first example of copper-catalyzed azomethine imine–alkyne cycloaddition (CuAIAC) was published only a year after the seminal papers of Meldal and Sharpless on Cu-catalyzed azide–alkyne cycloaddition (CuAAC), the CuAIAC reaction has remained overlooked by the synthetic community for almost a decade. Since 2010, however, CuAIAC reaction started to emerge as a promising supplement to the well-known CuAAC reaction. The present review surveys primarily the literature on CuAIAC reaction since 2003. Beside this, azomethine imine–alkyne cycloadditions catalyzed by other metals, selected examples of metal-free reactions, and related [3+3] and [3+4] cycloadditions of azomethine imines are presented. All these experimental data indicate the viability of CuAIAC in organic synthesis and the applicability in ‘click’ chemistry.1 Introduction2 Reactions with Acyclic Azomethine Imines3 Reactions with C,N-Cyclic Azomethine Imines4 Reactions with N,N-Cyclic Azomethine Imines5 Reactions with C,N,N-Cyclic Azomethine Imines6 The Mechanism of the CuAIAC Reaction7 Conclusions and Outlook
Keywords: azomethine imines; alkynes; cycloadditions; click chemistry; pyrazolines